Description of three new species of Hyalella Smith, 1874 (Crustacea: Amphipoda) from Southeast Mexico - Marrón-Becerra, Aurora; Hermoso-Salazar, Margarita (Zootaxa, 2023)
Lacandona tropical rainforest is an area with an important hydrological and biological role in Mexico, nevertheless there are few studies about freshwater macrofauna. In this study, we described three new species collected in three different water bodies in the Lacandona tropical rainforest: H. parva from lake Nahá with a minute body size without mucronations on pleonites 1–2, H. montebellensis from lake La Esmeralda with two dorsoposterior carinae on pleonites 1 and 2 (mucronations) and one seta almost at mid-ventral margin of gnathopod 1, and H. lacandonis from lake Península with minute dorsal mucronations on pleonites 1–2 and 2–3 setae on the hind margin of basis of gnathopod 1. Hyalella montebellensis n. sp. and H. lacandonis n. sp. have almost the same number of articles in flagellum of antennae 1–2, both species present four pappose setae on the inner plate of maxilla 1 and telson subquadrate, longer than wide.